ADMINSTRATIVE AND TERRITORIAL DESIGN OF THE REPUBLIC OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Nishonova Munisa Oltinbek qizi (TADQIQOTLAR.UZ, 2024)
Annotation:This article provides detailed information about the geographical and administrative structure of the Republic of Uzbekistan. It highlights the country’s location in Central Asia, its area, borders with neighboring countries, and the length of its borders. The article also mentions the regions of Uzbekistan, its Day of Independence, diplomatic relations with other countries, and the presence of foreign embassies in Tashkent.